Analysis of 3 Dimensional Space Modeling Building Shopping Center Market Aceh - Desita Ria Yusian TB; Khairunnisa Khairunnisa (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2018)
The 3 Dimensional (3D) modeling of an object has become one of the most important needs in many areas such as mapping, tourism, documentation, inventory, promotion, animation, film and so on because it has the advantages of 3D, interactive and representative display. 3D Spatial Modeling Building Shopping Center Pasar Aceh is designed because the absence of information that displays the entire spatial part the facilities contained in the Shopping Center Building in 3 Dimensions. In the process of making the material and texture is done by the process of giving color in accordance with the data that has been collected. The lighting process is required to provide a bright effect on the building. The final process done in 3D modeling is the process of rendering the image by choosing a resolution of 1600x1200 pixels which is the size of image resolution of the image rendering. Image rendering on 3D spatial modeling The Shopping Center building only displays a visual representation of the per-frame of the parts to be rendered. Form of visualization of the modeling is expected to provide new information to the visitors about the interior layout of the interior, exterior and the location of the facilities contained in the Building Shopping Center Pasar Aceh in the form of the final 3 Dimensions. Keywords : streaming multimedia, MPEG, peer-to-peer, VLC